2021
DOI: 10.17718/tojde.906468
|View full text |Cite
|
Sign up to set email alerts
|

Addressing Learner Cultural Diversity in Mooc Design and Delivery: Strategies and Practices of Experts

Abstract: This mixed-methods study investigates the design and instructional practices of massive open online courses (MOOCs) instructors within the learning environment to address the cultural diversity and learner personalization needs. Leveraging a grounded theory approach, the researchers analyzed two rounds of email interviews (n1= 25; n2=19) with MOOC and open education leaders about cultural sensitivity and personalization in MOOCs. Those interviews led to the formation of a 30-item online questionnaire completed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 43 publications
0
8
0
2
Order By: Relevance
“…The primary motivators for the MOOC instructors in our database included to experience teaching a MOOC and connect to a large and diverse audience (73%), explore innovations in online teaching and learning (73%) and increase learners’ access to higher education worldwide (70%). Many also hoped to build their institutional and personal reputation (60% and 42%, respectively) (Zhu et al ., ). Suffice to say, there are myriad motivational factors determining whether one decides to teach a MOOC.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…The primary motivators for the MOOC instructors in our database included to experience teaching a MOOC and connect to a large and diverse audience (73%), explore innovations in online teaching and learning (73%) and increase learners’ access to higher education worldwide (70%). Many also hoped to build their institutional and personal reputation (60% and 42%, respectively) (Zhu et al ., ). Suffice to say, there are myriad motivational factors determining whether one decides to teach a MOOC.…”
Section: Resultsmentioning
confidence: 97%
“…For instance, Zhu et al . () indicated that 58% of the 143 survey participants in that particular study had designed just one MOOC. The primary motivators for the MOOC instructors in our database included to experience teaching a MOOC and connect to a large and diverse audience (73%), explore innovations in online teaching and learning (73%) and increase learners’ access to higher education worldwide (70%).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Initially, MOOCs were used to meet the educational demands of adults (Arnavut et al, 2020;Zhu et al, 2021). Over time, the openness and flexibility of these technological tools led that universities design new courses to facilitate the teaching-learning process from any country (Zhu et al, 2021).…”
Section: Moocs and Ict In The Educational Fieldmentioning
confidence: 99%
“…Technological advances are changing the planning and organization of the courses under the distance and face-to-face modalities (Arnavut et al, 2020;Kim et al, 2021;Zhu et al, 2021). In particular, the incorporation of MOOCs in the school activities allows the creation of new virtual spaces for learning and teaching (Albelbisi et al, 2021;Kim et al, 2021;Lorente-Ruiz et al, 2021).…”
Section: Introductionmentioning
confidence: 99%